Electronic coffee grains separator (2011)
Accurate coffee sorting is a response to pressures for product quality and to a growing market for specialty coffees. One of the major challenges in this regard is to prepare the raw coffee fruits for sorting in one-by-one electronic machines. In this paper, we present a mechanical device developed to separate clusters and impurities from the main process. The mechanical device consists of two inclined belt conveyors with upward motion, working in series. This arrangement conveys upwards any elements with more than three contact points on the belt’s flat surface, while quasi-spherical elements (fruits) roll down on the belts. The experimental set up was designed to allow each belt’s inclination and speed to vary, in order to run a 3 x 3 factorial treatment design (Three inclinations: 10º, 14º and 18º and three speeds: 0.17, 0.20 and 0.24 m s-1). The belt transport surface material was PVC. The best performance was obtained at the speed of 0.20 m s-1 and between 10º and 14º of inclination. After these findings, three treatments were conducted at a working speed of 0.20 m s-1 and three inclinations between 10º and 14º, finding the best performance at 11º. In these conditions the mean efficacy of separation was 98.8%, varying within a range between 97.5% and 100%. The resulting system from this research work is suitable to run as pretreatment of one-by-one electronic sorters of coffee and coffee-like products.